The Resistance in Tribolium castaneum (Hbst.) against Phosphine and Deltamethrin - SHAHID, MUHAMMAD (Journal of Scientific Agriculture, 2019)
The red flour beetle Tribolium castaneum (Hbst.) is the most destructive pest of the stored grains and responsible for causing the tremendous loss to stored grains depends upon the storage structures and conditions. It deteriorates the quality and quantity of the stored grains. The current study was carried out to monitor the level of resistance in red flour beetle against phosphine and deltamethrin. Six concentrations of phosphine (0.006, 0.007, 0.008, 0.009, 0.01 and 0.011 ppm) and deltamethrin (0.01, 0.02, 0.03, 0.04, 0.05 and 0.06 ppm) were used against this test insect. The mortality data of this insect against phosphine was recorded after 7, 14 and 21 days of treatment. The data regarding mortality (%) was recorded after 24, 48 and 72 hours. The results showed that the maximum mortality of resistant and susceptible strain of T. castaneum against deltamethrin at 0.06% was 38.78% and 72.52% respectively. The maximum mortality of resistant and susceptible strain of T. castaneum against phosphine at 0.011 ppm was 74.46% and 76.81% respectively. All the data showed that Tribolium castaneum was 4.86 times fold resistant against deltamethrin after 72 hours’ time interval than over susceptible strains. The LC50 value showed that T. castaneum was 0.75 times fold resistant against phosphine after 7 days’ time interval than over susceptible strains